Phonetic Efforts by Dr. Abdul Sabour Shaheen - Muhammad Ali Mozan, Researcher. Zarqa; Kadhim Hassan, Prof. Assist .Dr. Suhair (Basra studies journal, 2024)
This Dr. Abdul Sabour Shaheen’s initial interest lies in studying phonetics and its branches in his books “In Linguistic Evolution”, “In General Linguistics”, and “Quranic Readings in Light of Modern Linguistics”. He also chose to translate the book “Phonetics” by the author “Bertil Malmberg” into Arabic because it is comprehensive, central, and simple, focusing on the fundamental issues in general phonetics. However, he tailored it to be more accessible to Arabic readers by adding marginal comments and attaching focused studies related to Arabic phonetics. Dr. Abdul Sabour Shaheen has explored aspects of abstract sound and its characteristics, dividing them into physiological phonetics, acoustic phonetics, and auditory phonetics. He also focused on studying the basic parts that play a significant role in human sound production, presenting the human speech apparatus, which is from inside to outside. He divided the speech apparatus into three main parts: the respiratory system, the larynx, and the supraglottic cavities, also subdividing them into secondary parts such as the palate, pharynx, among others.